PENGARUH WORK-LIFE BALANCE DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SMAN 3 PALOPO - Ketut Tiara Dewi; Kadek Riska Juwita; Ernalisa Ernalisa; Yuda Satria Nugraha; Khairunnisa Edy (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to determine the influence of work-life balance and job satisfaction on teacher performance at SMAN 3 Palopo. Specifically, it seeks to examine the impact of work-life balance on teacher performance and the impact of job satisfaction on teacher performance at the school. A quantitative research method was employed, with a sample consisting of 59 teachers from SMAN 3 Palopo. A saturated sampling technique was used for sample selection. Data collection involved three methods: interviews, observation, and questionnaires. Data analysis was conducted using multiple linear regression via SPSS software. The results indicate that, simultaneously, the variables of work-life balance and job satisfaction have a positive and significant effect on teacher performance at SMAN 3 Palopo. Individually, job satisfaction has a positive and significant effect on teacher performance. Meanwhile, work-life balance has a positive effect on teacher performance, though this effect is not statistically significant.